Eichhornia crassipes: an advantageous source of shikimic acid - Cardoso, Sthephanie F. (2014)
The water hyacinth (Eichhornia crassipes (Mart.) Solms, Pontederiaceae) is considered as one of the most productive plants on earth, and an aquatic weed, which causes serious environmental problems. In this study, this species is presented as an alternative of a renewable source of shikimic acid. Although this acid is an important intermediate in the biosynthesis of aromatic compounds in plants and microorganisms, its occurrence is described for the first time in a species of the Pontederiaceae family. Shikimic acid is the lead compound for the production of the antiviral agent oseltamivir phosphate (Tamiflu®). Semi-quantitative analyses of the plant extracts by HPLC-PDA showed that the aerial parts of E. crassipes contain higher shikimic acid concentration (0.03%-2.70% w/w) than the roots (0.05%-0.90% w/w), and that methanol is a better solvent than water for shikimic acid extraction.